Variacion del contenido en sangre durante el desarrollo del Boophilus microplus - Mella, C.M.=700 1 Acosta, A.; Revilla, P.; Polo, J.
(En, Es)
Ilus., 6 ref.
Keywords: TERNERO; BOOPHILUS MICROPULUS; ACARINA; IXODIDAE; SANGRE; INFESTACION; CUBA; PIRIDIN-HEMOCROMOGENOS; REVISTA DE SALUD ANIMAL